Students’ Mathematical Modeling Ability in AR-Assisted Geometry Learning - Elika Kurniadi; Putri Novita Sere Simanjuntak (Universitas Ma'arif Lampung, 2026)
This study aimed to describe ninth-grade students’ mathematical modeling abilities on cube and rectangular prism topics through Augmented Reality (AR)-assisted learning. This qualitative descriptive study involved 25 ninth-grade students at SMP PGRI 7 Palembang. Data were collected through mathematical modeling tests and semi-structured interviews. The analysis focused on four indicators: problem identification, mathematical model construction, problem solving, and interpretation of solutions. The findings revealed that most students demonstrated good mathematical modeling ability, particularly in visualization and model construction stages. AR media helped students understand three-dimensional concepts more concretely and supported the transformation of real situations into mathematical representations. However, several students still experienced difficulties in interpreting mathematical results into real-world contexts. Therefore, AR-assisted learning can be considered an alternative instructional strategy to improve students’ mathematical modeling abilities in geometry learning.